First observation of [sigma]- -e- elastic scattering in the hyperon beam experiment WA89 at CERN - Adamovič, M. I.; Siebert, Hans-Wolfgang (The European physical journal. C, Particles and fields, 1999)
We have investigated the elastic scattering of high energy Σ−Σ−Σ^- off electrons from carbon and copper targets using the CERN hyperon beam. Scattering events are identified using a maximum likelihood technique exploring the kinematical relations of the scattered particles. The observed Q22^2-distribution of these events suggests a mean square charge radius of the Σ−Σ−Σ^- of <r2ch>(Σ−)=0.91±0.32(stat.)±0.4<rch2>(Σ−)=0.91±0.32(stat.)±0.4 < r^2_{ch}>(Σ^-) = 0.91 ± 0.32 (stat.) ± 0.4 (syst.) fm22^2. This constitutes the first measurement of <r2ch>(Σ−)<rch2>(Σ−) < r^2_{ch}>(Σ^-) and demonstrates the possibility to also measure the charge radii of other hyperons.
Im Titel wird Sigma als griechischer Buchstabe dargestellt
Im Titel sind die Minuszeichen nach Sigma und e hochgestellt
Gesehen am 27.02.2020